Censor [videorecording (DVD)] - Bailey-Bond, Prano; Bailey-Bond, Prano; Algar, Niamh; Smiley, Michael, 1963-; Burns, Nicholas, 1977- (Magnolia Home Entertainment, 2021)
After viewing a strangely familiar video nasty, Enid, a film censor, sets out to solve the past mystery of her sister's disappearance, embarking on a quest that dissolves the line between fiction and reality.